Monitoring of Physical Processes in Upper Atmosphere, Ionosphere and Magnetosphere in Ionosphere Space Missions - Petrukovich Anatoly (EDP Sciences, 2021)
The Ionosphere missions are the part of Ionosond-2025 space project, which main scientific objectives are monitoring of physical processes in the Earth upper atmosphere, ionosphere and magnetosphere, as well as of solar activity. Within the framework of the Ionozond-2025 project, it is planned to launch four spacecraft Ionosphere and one satellite Zond. The Zond satellite is planned to be launched in 2025. The main task of Zond mission is patrol of solar activity. The launch of the first pair of spacecraft is planned in early 2022, the second pair - late 2022 or early 2023. In case of successful implementation of the program of experiments on the Ionosphere satellites, control of the physical parameters of electromagnetic fields and corpuscular radiation in the near-Earth space will be provided, new information will be obtained on the geophysical processes occurring in the magnetosphere, ionosphere and upper atmosphere in their connection with solar activity.